Hukou status and perinatal depression: a longitudinal cohort study in China - Zhou, Tingting; Sun, Ying; Chen, Fangyuan; Yang, Xiuping; Jiang, Chen; Gu, Xuejun (Frontiers in Public Health, 2025)
ObjectivesPerinatal depression (PND) is a significant public health concern, particularly among those without local household registration. This study aims to investigate the association between China’s hukou status (household registration system) and PND, and to assess whether socioeconomic status (SES) modifies this relationship.MethodsA prospective cohort study was conducted among 1,825 pregnant women at four maternal and child health hospitals in Ningbo, China, from January to December 2022. Depressive symptoms were assessed by the Edinburgh Postnatal Depression Scale (EPDS) during each trimester and postpartum. Socioeconomic status (SES) was assessed via a 0–5 composite score comprising educational level, household monthly income, and employment status. Generalized Estimating Equations (GEE) were used to evaluate the association between hukou status and PND (EPDS ≥ 9), and to examine potential effect modification by SES. All models were verified in parallel using logistic regression analyses. The robustness of the associations was examined in sensitivity analysis using alternative EPDS thresholds (≥10 and ≥13).ResultsIn our study, local hukou status was significantly associated with a lower prevalence of PND compared with non-local hukou status (adjusted odds ratio [aOR] = 0.30, 95% CI: 0.22–0.42; p < 0.001), with the strongest protective effect observed in the second trimester (aOR = 0.28, 95% CI: 0.20–0.38). However, the interaction between hukou status and time was not statistically significant (p > 0.05). Interaction analyses between hukou status and SES further confirmed that the protective effect of local hukou was independent of SES (p > 0.05). Among the 1,825 pregnant women included, 345 (18.9%) held non-local hukou, and the prevalence of depression was 285 (15.62%), 237 (12.99%), 257 (14.08%), and 167 (9.15%) cases in the first, second, third trimesters, and postpartum period, respectively. Sensitivity analyses verified the robustness of all aforementioned findings.ConclusionChina’s hukou status functions as an independent institutional determinant of PND risk, with its protective effect unmodified by individual socioeconomic resources. Addressing the hukou-based institutional inequities is essential for developing effective public health strategies and clinical interventions against PND.